Impact of Universitas Trunojoyo Madura anthem on student engagement and loyalty: A thematic analysis within Indonesian higher education - Saksono Suryo Tri; Endriyati Enni (BIO Web of Conferences)
University anthems are often considered symbols of institutional identity and pride. This study investigates how the Universitas Trunojoyo Madura anthem influences student engagement and loyalty, examining its role in fostering a sense of community and institutional pride, where the anthem potentially enhances student involvement by strengthening a sense of community and identification with the university. While previous research on university anthems has largely been confined to Western contexts, this study explores the effects of such cultural symbols within Indonesian higher education, focusing specifically on Universitas Trunojoyo Madura. The study employs thematic analysis of data collected from in-depth interviews and focus groups with students. An empirical normative approach is used to systematically gather and analyze qualitative data. Findings reveal that regular exposure to the anthem positively affects students' perceptions of the university, increases their attachment to university values, and enhances their loyalty. The anthem functions as a potent communication tool that promotes the university’s core values and reinforces students’ sense of communal identity. This suggests that cultural symbols can significantly enhance student engagement and loyalty. This study provides evidence that cultural symbols in higher education can enhance student engagement and loyalty and strengthen their relationship with the institution. These findings imply that universities can leverage cultural symbols, such as anthems, to bolster institutional identity and improve student engagement and loyalty.